Automated solar tracking system for increasing solar irradiance capture to improve power generation - Tarafder, Arnob; Abrar, Mohammad Mahir; Mondol, Md. Arefeen; Chowdhury, Niloy Roy (Brac University, 2023)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.